Primera cita de Parthenocissus tricuspidata y nuevo registro de P. quinquefolia (Vitaceae) adventicias en la Argentina - Hurrell, Julio Alberto (2012)
This paper includes two adventitious species of the genus Parthenocissus Planch. in Argentina: P. tricuspidata (Siebold & Zucc.) Planch. and P. quinquefolia (L.) Planch., both introduced as ornamentals. Descriptions, synonymy, iconography, distribution, common names, uses, keys and reference material are given. Also contains observations about its climb strategies, its expansion mechanisms, and its actual status in the context of naturalization process.